Peningkatan Jumlah Prototipe Produk Hasil Riset Universitas Andalas - Cesar Welya Refdi; Wenny Surya Murtius (Warta Pengabdian Andalas, 2020)
Innovation products are new ideas and ideas generated, one of the results of research.Universities are limited to only lead to the results of research and publications. Prototype development is one solution to maximize research results so that it can be utilized and commercialized. With the proper funding, a strategy can accelerate the downstream process of research results and break down the obstacles that are causing the failure of the innovation process. The purpose of this program is a prototype as a media for the dissemination of research products from university and the availability of innovative research products from Andalas University. The resulting product prototype will be displayed in a showroom, and become a visual aid. The method used is data collection of potential products to be produced, collaboration with inventors, the prototype production, product improvement, and socialization by joining bazaar. The number of prototypes produced totaled 36 types of products, which went through the consultation stages of forms, types of packaging and labeling. Increasing the number of prototypes obtained from this research can increase the desire of researchers to improve applied research that can benefit human life, and it is expected to lead to the government's confidence in higher education innovation products.